Análise conceitual sobre as relações semânticas em ciência da informação: contribuições para o desenvolvimento de ontologias - Julia Aparecida Goncalves Campos (2009)
It was verified the lack of systemized methods for the conceptual model in the ontology building process This process, intellectual in its nature, is associated with others techniques and involves the identification, the determination, the structuring and the validation of the concepts and semantic relations appropriated for the knowledge representation. Different from the traditional tools for the knowledge representations, ontologies have no predefined and limited structure of semantic relations, but instead, allow refined semantic relations be incorporated in its structure, according to the necessity of representation and the knowledge dynamic. Because of that, a posteriori analyses of the knowledge domains to be represented are essential for the identification of new semantic relations. Considering the possibility of identification of a priori structure of semantic relations, the objective of this study was to be a reference to new ontology building projects and to validate the applied methodology to the determination of semantic relations. As a result, it was identified that there is not prevalent of unique approaches (either a priori or a posteriori), but there is the necessity of combined methods to a better identification of the dominion conceptualization. The proposed method in the methodology was the conceptual analysis with the application of the Dahlbergs Concept Theory, where, from the existing definitions in the literature for the semantic relations, it was possible to determine the characteristics of each concept in a discerning way. As a principal result in this research, it was identified five groups of semantic relations (equivalence relations; hierarchy relations; partitive relations; cause-effect relations and associative relations. In counterpart, for information science, researches of this nature corroborate for the methodological production in this area and for the improvement of the techniques for the organization and recovery of the information, in response of the real necessities of the information representation in digital ambient..